Beliefs and practices among primary care physicians during the first wave of the COVID-19 pandemic in Baden-Wuerttemberg (Germany): an observational study - Roth, Catharina; Breckner, Amanda; Möllinger, Sophia; Schwill, Simon; Peters-Klimm, Frank; Szecsenyi, Joachim; Stengel, Sandra; Wensing, Michel (BMC family practice, 2021)
During the first wave of the COVID-19 pandemic various ambulatory health care models (SARS-CoV-2 contact points: Subspecialised Primary Care Practices, Fever Clinics, and Special Places for Corona-Testing) were organised in a short period in Baden-Wuerttemberg, a region in Southern Germany. The aim of these SARS-CoV-2 contact points was to ensure medical treatment for patients with (suspected) and without SARS-CoV-2 infection. The present study aimed to assess the beliefs and practices of primary care physicians who either led a Subspecialised Primary Care Practice or a Primary Care Practice providing care as usual in Baden-Wuerttemberg during the first wave of the COVID-19 pandemic.